2020
DOI: 10.1021/acs.energyfuels.0c00278
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Absolute Adsorption of CH4, n-C4H10, and CO2 on Shale

Abstract: Comprehensive knowledge of the absolute adsorption of light hydrocarbons and CO 2 is significant for shale reservoir assessment and CO 2 stimulation optimization. In this work, excess adsorption isotherms are first obtained for CH 4 , n-C 4 H 10 , and CO 2 on typical shale. The simplified local density (SLD) theory is then used to obtain the adsorption-phase density for CH 4 , n-C 4 H 10 , and CO 2 in organic pores, which is then employed for absolute adsorption calculation. The absolute adsorption of CH 4 , n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Since the 1980s, NMR technology has been widely used to observe the fluid distribution and pore volume changes under different environmental conditions. āˆ’ This technique can quantitatively characterize the change in the core pore volume parameters by measuring the transverse relaxation T 2 distribution of the sample; the two have a good corresponding relationship. āˆ’ The NMR T 2 value reflects the size of the specific surface of the rock pore throat, which is proportional to the pore throat radius, indicating that a larger T 2 value corresponds to a larger core pore throat …”
Section: Resultsmentioning
confidence: 99%
“…Since the 1980s, NMR technology has been widely used to observe the fluid distribution and pore volume changes under different environmental conditions. āˆ’ This technique can quantitatively characterize the change in the core pore volume parameters by measuring the transverse relaxation T 2 distribution of the sample; the two have a good corresponding relationship. āˆ’ The NMR T 2 value reflects the size of the specific surface of the rock pore throat, which is proportional to the pore throat radius, indicating that a larger T 2 value corresponds to a larger core pore throat …”
Section: Resultsmentioning
confidence: 99%
“…Besides, the pore space would be too small to accommodate large amounts of CO 2 for storage. On the other hand, organic-rich shale rocks can adsorb CO 2 on organic matter, ,,āˆ’ enabling an effective mechanism for retaining CO 2 in rocks. Because adsorbed CO 2 molecules are more densely packed and tightly held than in the free phase, adsorption of CO 2 in shale is a favorable scenario for a combined CO 2 enhanced recovery and CO 2 storage process.…”
Section: Introductionmentioning
confidence: 99%
“…Injecting CO 2 into shale gas reservoirs has been adopted as a suitable method for enhanced CH 4 recovery. As the dominant gas component, CH 4 recovery as a result of CO 2 injection is most investigated. āˆ’ With the measurement of adsorption isotherms of CH 4 and CO 2 , it was found that CO 2 has higher adsorption capacity than CH 4 ; it implies that CO 2 could be a suitable agent for developing shale gas reservoirs. āˆ’ In recent years, molecular simulation methods, such as molecular dynamic simulation, density functional theory, etc., are powerful in investigating the microphase behavior of fluids in nanopores. ,āˆ’ On the basis of the molecular simulation results, CO 2 generally forms stronger adsorption layers on the shale surface compared to CH 4 , validating the efficiency of CO 2 for CH 4 recovery.…”
Section: Introductionmentioning
confidence: 99%